Combinatorial effects of quercetin and sex-steroids on fluid and electrolytes’ (Na+, Cl-, HCO3-) secretory mechanisms in the uterus of ovariectomised female Sprague-Dawley rats - Shahzad, H.; Giribabu, N.; Karim, K.; Kassim, N.M.; Muniandy, S.; Salleh, N. (Public Library of Science, 2017)
Dysregulation of uterine fluid environment could impair successful reproduction and this could be due to the effect of environmental estrogens. Therefore, in this study, effect of quercetin, an environmental estrogen on uterine fluid and electrolytes concentrations were investigated under sex-steroid influence. Ovariectomised adult female Sprague-Dawley rats were given 10, 50 or 100mg/kg/day quercetin subcutaneously with 17-β estradiol (E) for seven days or three days E, then three days E plus progesterone (P) (E+P) treatment. Uterine fluid secretion rate, Na+, Cl- and HCO3 - concentrations were determined by in-vivo perfusion. Following sacrifice, uteri were harvested and levels of the proteins of interest were identified by Western blotting and Realtime PCR. Distribution of these proteins in the uterus was observed by immunofluorescence. Levels of uterine cAMP were measured by enzyme-linked immunoassay (EIA). Administration of quercetin at increasing doses increased uterine fluid secretion rate, Na+, Cl- and HCO3 - concentrations, but to the levels lesser than that of E. In concordant, levels of CFTR, SLC4A4, ENaC (α, β and γ), Na+/K+-ATPase, GPα/β, AC and cAMP in the uterus increased following increased in the doses of quercetin. Co-administration of quercetin with E caused uterine fluid secretion rate, Na+, Cl- and HCO3 - concentrations to decrease. In concordant, uterine CFTR, SLC26A6, SLC4A4, ENaC (α, β and γ), Na+/K+-ATPase, GPα/β, AC and cAMP decreased. Greatest effects were observed following co-administration of 10mg/kg/day quercetin with E. Co-administration of quercetin with E+P caused uterine fluid Na+ and HCO3 - concentrations to increase but no changes in fluid secretion rate and Cl- concentration were observed. Co-administration of high dose quercetin (100 mg/kg/day) with E+P caused uterine CFTR, SLC26A6, AC, GPα/β and ENaC (α, β and γ) to increase. Quercetin-induced changes in the uterine fluid secretion rate and electrolytes concentrations could potentially affect the uterine reproductive functions under female sex-steroid influence.